Near death experiences: a multidisciplinary hypothesis - Bokkon, Istvan; Mallick, Birendra N.; Tuszynski, Jack A. (Frontiers in Human Neuroscience, 2013)
Recently, we proposed a novel biophysical concept regarding on the appearance of brilliant lights during near death experiences (NDEs) (Bókkon and Salari, 2012). Specifically, perceiving brilliant light in NDEs has been proposed to arise due to the reperfusion that produces unregulated overproduction of free radicals and energetically excited molecules that can generate a transient enhancement of bioluminescent biophotons in different areas of the brain, including retinotopic visual areas. If this excess of bioluminescent photon emission exceeds a threshold in retinotopic visual areas, this can appear as (phosphene) lights because the brain interprets these intrinsic retinotopic bioluminescent photons as if they originated from the external physical world. Here, we review relevant literature that reported experimental studies (Imaizumi et al., 1984; Suzuki et al., 1985) that essentially support our previously published conception, i.e. that seeing lights in NDEs may be due to the transient enhancement of bioluminescent biophotons. Next, we briefly describe our biophysical visual representation model that may explain brilliant lights experienced during NDEs (by phosphenes as biophotons) and REM sleep associated dream-like intrinsic visual imageries through biophotons in NDEs. Finally, we link our biophysical visual representation notion to self-consciousness that may involve extremely low-energy quantum entanglements. This article is intended to introduce novel concepts for discussion and does not pretend to give the ultimate explanation for the currently unanswerable questions about matter, life and soul; their creation and their interrelationship.